AIRCRAFT AND THEIR MAIN ELEMENTS - Tashkent Chilonzor 1-sonl Politexnikum Original article Kadirov Asqar Anvarovich-Senior Lecturer (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Currently, UAVs (Unmanned Aerial Vehicles) have filled a large area of ​​our life: military, civil, space, medical, logistic, etc. In the scientific field, work continues on upgrading existing and developing new drones for more efficient performance of the tasks assigned to the drone. The purpose of this work is to study the use of UAVs (quadcopters), consider its main elements, and cons truct a mathematical model of a quadcopter. Keywords: UAV, drone, quadcopter